Analisis Perubahan K13 ke Kurikulum Merdeka Belajar terhadap Proses Belajar Siswa di SDN Lidah Wetan II - Sa’diah, Muslikhatus; Putri, Della Nurmaliana; Hasanah, Putri Maulidatul; Purnomo, Acni Keyrina (Lembaga Yasin AlSys, 2023)
The purpose of this study is to determine the impact of curriculum changes from K13 to the independent learning curriculum on the learning process at SDN Lidah Wetan II, Surabaya. This research was conducted using a descriptive qualitative approach, this approach was carried out on the grounds that the researcher considered that to realise the objectives of this research it was most appropriate to use descriptive qualitative research. The subjects of this study were the deputy head of curriculum and grade V teachers at SDN Lidah Wetan II. The methods used in data collection were observation, interview, and documentation. Data analysis was carried out using the Miles and Huberman model with a sequence of data collection, data condensation, and conclusion drawing. The results of this study discuss the differences between the 2013 curriculum and the independent learning curriculum at SDN Lidah Wetan II, where the differences lie in curriculum planning; the positive and negative impacts of curriculum change; and the challenges experienced by teachers and students in implementing the independent learning curriculum at SDN Lidah Wetan II